Analysis of hope level and its influencing factors in patients with decompensated cirrhosis. Issue 2 (22nd August 2022) - Zhang, Yuanyuan; Xie, Ling; Li, Fen; Huo, Chunyan; Miao, Yanling; Wang, Lining; Ding, Caiyan
Abstract: Aim: The aim of this study was to examine hope level and its influencing factors in patients with decompensated liver cirrhosis. Design: A prospective observational study. Methods: We selected 93 patients with decompensated liver cirrhosis from a Chinese university hospital based on the inclusion and exclusion criteria. A general information questionnaire and Herth Hope Index were used, and multiple linear regression identified factors associated with the patients' hope level. Results: The participants' average hope level was 32.01 ± 6.14 (moderate). The hope score's highest and lowest dimensions were "interconnectedness" (11.29 ± 2.17) and "temporality and future" (10.12 ± 2.28), respectively. Multiple linear regression showed that education level and monthly per capita income were independent influencing factors ( p  < .05). These variables explained 38.3% of the variation in hope. Conclusion: The participants' hope level was not optimal. Thus, medical staff should pay special attention to patients with low education level and poor economic status, and guide them to adopt a positive attitude.